ANALISIS POLA PERSEBARAN PENYAKIT TB PARU DI KOTA PARIAMAN - fernando hero alyandri; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to analyze: 1) To determine the pattern of the spread of pulmonary tuberculosis in the City of Pariaman 2) To determine the level of susceptibility of pulmonary tuberculosis in Pariaman City 3) To determine the characteristics of the area of ​​pulmonary tuberculosis in Kota Pariaman 4) To determine the estimated incidence of pulmonary tuberculosis in Kota Pariaman. This type of research is descriptive with the aim of describing the pattern of distribution of pulmonary tuberculosis patients in Kota Pariaman. The population of this study were all people affected by pulmonary tuberculosis in Kota Pariaman. The total population of this study was 167 people from 2015-2019. Data collection using secondary data and survey the location of pulmonary tuberculosis patients according to the patient's address. The results of this study found that 1) Mapping the distribution of pulmonary tuberculosis patients in Central Pariaman District, there were 42% of pulmonary tuberculosis patients 2) Judging from the estimated kernel for 2015-2019 the direction of the distribution of pulmonary tuberculosis in Kota Pariaman is in the city center, namely Central Pariaman District 3) The results of the level of vulnerability of pulmonary tuberculosis in Pariaman City are also in the city center, namely in Central Pariaman District and North Pariaman District, which are in the red zone.